Analisis Efektivitas Biaya Pasien Hipertensi Di Klinik Milla Husada - Nur Cahyani Novitasari Novitasari; Risma Sakti Pambudi; Khotimatul Khusna (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2024)
Hypertension is still a health problem in the world. Most hypertensive patients cannot control their blood pressure, while the cost of treatment is increasing every year, so it is necessary to carry out an analysis to find out which drugs are most cost effective and provide the best therapeutic outcomes. This study aims to determine the cost effectiveness of hypertensive patients at the Milla Husada clinic. The research was carried out descriptively by taking data retrospectively from medical records. The sample in this study was 38 patients from medical record data of hypertensive patients who were hospitalized at the Milla Husada Clinic in 2023 and data on drug use was obtained from the pharmacy installation. The data obtained was then subjected to CEA (Cost Effectiveness Analysis) analysis using the ACER (Average Cost Effectiveness Ratio) formula. The results of the study showed that the effectiveness of therapy in hospitalized general patients and BPJS for the ACEI and diuretic drug classes was the same as 57.14%. Meanwhile, the cost effectiveness value of using antihypertensive combination therapy in general inpatients with a combination of ACEI and diuretic drugs is with an ACER value of IDR 2,281,125 and for BPJS inpatients with a combination of ACEI and diuretic drugs with an ACER value of IDR 2,341,617. The conclusion of this study is that the combination of ACEI and diuretic drugs is more effective than other drug combinations. Keywords: Effectiveness; Cost; CEA; Hypertension